APLIKASI TEKNOLOGI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK ANALISIS TINGKAT KERENTANAN TSUNAMI DI KECAMATAN MAMUJU - Asri, Haryanto; Yusuf, Muhammad (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
This research aims to analyze the vulnerability to tsunami disasters in Mamuju District, West Sulawesi, using remote sensing technology and Geographic Information Systems (GIS). Mamuju District is at high risk of tsunamis due to its coastal location and its position between active tectonic plates. The analysis utilizes five main parameters: elevation, slope gradient, distance from rivers, distance from the coastline, and land cover. The GIS overlay analysis method is applied to map tsunami hazard zones, combining weighting and scoring for each parameter. The results indicate that 3% of the area has very high vulnerability, 7% of the area has high vulnerability, while 82% of the area has low to very low vulnerability. Areas with very high vulnerability include the coastal zone directly adjacent to the shoreline and residential areas. This study is expected to serve as a reference for local governments and disaster management agencies in efforts to mitigate and plan safer spatial arrangements against tsunami threats. Mitigation strategy recommendations include the construction of evacuation routes, safe shelters, and the regular enhancement of disaster education and simulations for the community. Furthermore, this research encourages the use of mountainous areas as primary evacuation zones and collaboration with research institutions for the development of more innovative mitigation technologies.